2020
DOI: 10.1007/s42399-020-00460-4
|View full text |Cite
|
Sign up to set email alerts
|

Labile PT-INR in a Covid-19 Patient Under Long-term Vitamin K Antagonist Therapy: a Case Report

Abstract: The COronaVIrus Disease-19 (COVID-19) has been associated with thromboembolic complications, but evidence on its impact on hemorrhagic risk are still scarce. We describe a case of COVID-19 with hemorrhagic complication in the post-acute phase of the disease. The patient was a 93-year-old woman admitted to a post-acute care unit for COVID-19 patients in northern Italy. The patient’s medical history included moderate cognitive impairment, atrial fibrillation under oral anticoagulation (warfarin 2.5 mg and 3.75 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…[ 19 ] Moreover, a single case report showed that even in the postacute phase of COVID-19, patients on warfarin therapy may have liable INR. [ 20 ] These findings add to the complexity of interpreting INR results in patients on warfarin complicated by COVID-19.…”
Section: Advantages Of Non-vitamin K Antagonist Oral Anticoagulants O...mentioning
confidence: 99%
“…[ 19 ] Moreover, a single case report showed that even in the postacute phase of COVID-19, patients on warfarin therapy may have liable INR. [ 20 ] These findings add to the complexity of interpreting INR results in patients on warfarin complicated by COVID-19.…”
Section: Advantages Of Non-vitamin K Antagonist Oral Anticoagulants O...mentioning
confidence: 99%
“…Tang et al also reported longer PT values in non-surviving patients with COVID-19 pneumonia in addition to higher D-dimer levels with fibrinogen degradation products (FDP) [ 8 ]. Additionally, a study presented by Trevisan et al enunciated the significance of prolonged PT in predicting the level of hemorrhagic risk in critical COVID-affected cases [ 19 ]. A 93-year-old woman (already under OAT), in the post-acute phase of the disease, presented a marked elevation of PT-INR of 25.1, supporting a strong impact of the infection on the coagulative pattern and a state of critical coagulopathy [ 19 ].…”
Section: Clinical Relevance Of Pt In Thromboembolic Complications and Covid-19 Associated Coagulopathy Cacmentioning
confidence: 99%
“…Additionally, a study presented by Trevisan et al enunciated the significance of prolonged PT in predicting the level of hemorrhagic risk in critical COVID-affected cases [ 19 ]. A 93-year-old woman (already under OAT), in the post-acute phase of the disease, presented a marked elevation of PT-INR of 25.1, supporting a strong impact of the infection on the coagulative pattern and a state of critical coagulopathy [ 19 ]. This patient was provided an immediate venous infusion of three-factor prothrombin complex concentrate and vitamin K until PT-INR reduction started to happen.…”
Section: Clinical Relevance Of Pt In Thromboembolic Complications and Covid-19 Associated Coagulopathy Cacmentioning
confidence: 99%
See 2 more Smart Citations